Protection of the environment: the scientific and moral commitment - Magnavita, Nicola (Medicina e Morale, 1990)
The protection of the environment requires the involvement of both scientific and humanistic disciplines, and strong moral obligation. This article aims to clarify the role and the limits of the scientific disciplines in the debate on the policies for the protection of the environment. The author also presents some considerations on the ecological committment required by Catholic ethics. Finally, two specific cases, concerning lead pollution and biotechnology, are studied.